Sustainable Tourism in Kerala: An Analysis of Development Models, Challenges, and Strategic Imperatives - Anas, Muhammed; Hans, V. Basil; V, Sini.; Ghimire, Mayanath; Neupane, Dasarath (NPRC Journal of Multidisciplinary Research, 2025)
Background: Kerala, a state in southwestern India branded as "God's Own Country," is globally recognized as a successful tourism model. Its strategic development, leveraging diverse natural assets and cultural heritage, has made tourism a primary contributor to its economy. However, this rapid growth has concurrently generated significant sustainability challenges that threaten the sector's long-term viability.Objectives: This study aims to conduct a comprehensive analysis of the Kerala tourism model. Its specific objectives are to: (1) identify the key pillars of its successful development, (2) critically examine the emergent environmental, socio-cultural, and economic challenges, and (3) propose strategic recommendations for a sustainable and resilient future.Methods: The research employed a systematic literature review methodology. A thorough analysis of academic peer-reviewed journals, government reports, and credible policy documents was conducted. Thematic analysis was used to synthesize the findings and identify core patterns and insights related to the research objectives.Findings: The analysis reveals that Kerala's success is built on strategic government policy, effective branding, and the diversification of its tourism products, including backwaters, hill stations, Ayurvedic wellness, and culinary tourism. However, key challenges identified include environmental degradation (e.g., pollution, resource strain), overtourism in popular destinations, risks of cultural erosion, and systemic vulnerabilities exposed by crises like the COVID-19 pandemic.Conclusion: The study concludes that while the Kerala tourism model is a notable success story, it has reached a critical juncture. The current trajectory of growth is unsustainable without a fundamental shift towards integrating robust sustainability principles and digital innovation into its core strategy.Implication: The findings imply that policymakers and industry stakeholders must prioritize sustainable governance, decentralize tourism, enhance community participation, and accelerate digital integration. Implementing these recommendations is crucial for ensuring the long-term resilience, inclusivity, and environmental sustainability of Kerala's vital tourism industry.